MATHEMATICAL UNDERSTANDING AND REPRESENTATION ABILITY OF PUBLIC JUNIOR HIGH SCHOOL IN NORTH SUMATRA - Minarni, Ani; Napitupulu, Elvis; Husein, Rahmad (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2016)
This paper is the result of first phase of the research about the development of studentsÃ¢â‚¬â„¢Ã‚Â mathematical understanding and representation ability through Joyful Problem-based LearningÃ‚Â (JPBL) at Public Junior High School in North Sumatera, Indonesia. The population is all of theÃ‚Â students of public junior high school (PJHS) in North Sumatera. Samples choose based onÃ‚Â stratified random sampling. The samples are the students of PJHS 27 Medan, PJHS 1 PercutÃ‚Â Sei Tuan, PJHS 1 Tebing Tinggi, and PJHS 2 Pematangsiantar. The techniques used forÃ‚Â collecting data is observation, interview, and essay test. The research findings: (1) Based onÃ‚Â interview and observation found that conventional approach still use in all of the class of PJHS;Ã‚Â The students engagement in learning activity is very low as well as students self-regulatedÃ‚Â learning; Most of the students do not attain minimal mastery achievement, (2) Based on essayÃ‚Â test found that achievement of the students in mathematical understanding and representationÃ‚Â test is categories low.Keywords: mathematical understanding, mathematical representation, joyful problem-based learningÃ‚Â DOI: http://dx.doi.org/10.22342/jme.7.1.2816.43-56